A Metaheuristic Algorithm for the Location Routing Problem with Heterogeneous Fleet (2014)
This paper considers the Location-Routing Problem with Heterogeneous Fleet (LRPH), in which the aim is to determine the depots to be opened, the customers to be assigned to each open depot, and the routes to be performed to fulfill the demand of the custo